The prevalence of dry eye in a very old population - Bikbov, Mukharram; Kazakbaeva, Gyulli M.; Rakhimova, Ellina M.; Rusakova, Iuliia A.; Fakhretdinova, Albina A.; Tuliakova, Azaliia M.; Panda-Jonas, Songhomitra; Gilmanshin, Timur R.; Zainullin, Rinat M.; Bolshakova, Natalia I.; Safiullina, Kamilia R.; Gizzatov, Ainur V.; et al. (Acta ophthalmologica, 2022)
Purpose To assess the prevalence of dry eye disease (DED) and Meibomian gland dysfunction (MGD) in a very old population. Methods The Ural Very Old Study (UVOS), a population-based cohort study performed in rural and urban Bashkortostan/Russia, included 1526 (81.1%) out of 1882 eligible individuals aged 85+ years. The participants underwent a detailed medical and ophthalmological examination including Schirmer´s test, slit-lamp based assessment of the Meibomian glands and an interview. Results The study included 1493 (97.8%) individuals with available information about DED (mean age: 88.3 ± 2.9 years). Schirmer´s test was ≤5 mm in 388 individuals (34.3%; 95% confidence interval (CI): 31.5, 37.1), and the mean score of subjective dry eye symptoms was 7.52 ± 2.14 (median: 6; range: 6-18; 95%CI: 7.41, 7.63). An MGD grade 1, 2, 3 and 4 was diagnosed in 367 (31.4%), 309 (26.4%), 89 (7.6%) and 39 (3.3%) eyes, respectively. The prevalence of DED diagnosis definition #2 (dry eye score ≥8, Schirmer´s test ≤5 mm) and definition #4 (dry eye score ≥7, Schirmer test ≤5 mm, MGD grade 1+), were 164/1132 (14.5%; 95%CI: 12.4, 16.5), and 167/1131 (14.8%; 95%CI: 12.7, 16.8), respectively. In multivariate analysis, higher DED prevalence was associated with female sex (odds ratio (OR): 2.36; 95%CI: 1.18, 4.71; p = 0.02), rural region of habitation (OR: 2.72; 95%CI: 1.10, 6.70; p = 0.03), longer axial length (OR: 1.30; 95%CI: 1.04,1.62; p = 0.02), higher hearing loss score (OR: 1.03; 95%CI: 1.01, 1.05; p = 0.001) and lower self-reported salt consumption (OR: 0.64; 95%CI: 0.54, 0.75; p < 0.001). Conclusions In this population-based recruited very old study sample aged 85+ years, higher DED prevalence (dry eye score ≥8, Schirmer´s test <5 mm; mean: 14.5%) and MGD prevalence (any grade:68.8%) was associated with female sex, rural region of habitation, longer axial length, higher hearing loss score and lower salt consumption.
Gesehen am 14.12.2022